Science fair projects : flight, space & astronomy - Bonnet, Robert L.; local; Keen, Dan. (New York : Sterling Pub., 1997)
Presents fifty-three simple experiments and projects revolving around space science, including topics such as seasons
Includes index.
School Library Journal
The Science Teacher (N.S.T.A.)
, the night sky, light, and flight.
Follett Library Resources
Keywords: 3-6; sears -- Space sciences -- Experiments; Juvenile literature. -- Astronautics -- Experiments; Juvenile literature. -- Astronomy -- Experiments; Juvenile literature. -- Science -- Exhibitions; Juvenile literature. -- Science projects; Juvenile literature. -- Space sciences; Experiments; Experiments; Science projects. -- Space sciences; sears; sears; sears